Intensive pig farming: Ethical considerations - Elena Lara de la Casa (Universitat Autonoma de Barcelona. Facultat de Dret, 2017)
Pork is the most widely consumed meat in the world. To produce the quantities of pig meat needed to meet customer demand, pig farms have become industrialized systems and hundreds of millions of pigs around the world are kept in these factories. The author highlights the main knowledge on natural pigs behavior as well as the psychological characteristics of pigs like cognitive skills, intelligence and their capacity to feel emotions. Also, conditions of the intensive indoor systems and the consequences for pig welfare are summarized. Finally, and based on this information, intensive farming conditions are analyzed and discussed from an ethical point of view.